Student Conceptual Mastery on Momentum and Impulse Materials in Problem Based Learning Models Assisted by Thinking Map - Miksandri Eksanita; Parno Parno; Markus Diantoro (Pascasarjana Universitas Negeri Malang (UM), 2021)
Abstract: The ability to master concepts can be developed with the Problem Based Learning model assisted by Thinking Map. The purpose of this study is to find out how the Problem Based Learning model assisted by Thinking Map influences the mastery of the concept of high school students on momentum and impulse. This research was conducted at SMAN 1 Bombana class X, the subject of this study was 30 students. This research is a mixed-method embedded experimental model. The test of mastery of concepts in the form of multiple-choice as many as 25 items with the Cronbach's alpha value was 0.715. Data analysis using t-test and obtained a value of 0,000 which shows that there is an influence between mastery of the concept and problem-based learning assisted by thinking map. Abstrak: Kemampuan penguasaan konsep dapat dikembangkan dengan model pembelajaran Problem Based Learning berbantuan Thinking map. Tujuan dari penelitian ini ialah untuk mengetahui perkembangan penguasaan konsep siswa setelah dibelajarkan dengan model pembelajaran Problem Based Learning berbantuan Thinking map pada materi momentum dan impuls. Penelitian ini dilakukan di SMAN 1 Bombana kelas X, dan subjek penelitian ini berjumlah 30 orang. Penelitian ini berjenis mixed method embedded experimental model. Instrumen penelitian ini adalah tes penguasaan konsep yang berupa soal jenis pilihan ganda sebanyak 25 butir soal dengan reliabilitas alpha Cronbach’s sebesar 0,715. Data dianalisis dengan menggunakan uji-t dan menghasilkan Sig. 0,000 yang menunjukkan bahwa ada perbedaan signifikan antara penguasaan konsep siswa sebelum dan sesudah mendapatkan pembelajaran problem based learning berbantuan thinking pada materi momentum dan impuls